A Qualitative Systematic Review of Pediatric Patient and Caregiver Perspectives on Pain Management for Vaso-Occlusive Episodes in the Emergency Department. Issue 3 (1st March 2023) - Lapite, Ajibike; Lavina, Ilana; Goel, Swati; Umana, Jasmine; Ellison, Angela M.
Abstract : Objectives: The primary objective of this study is to describe the experiences of pediatric patients with sickle cell disease (SCD) and their caregivers who have presented to the emergency department (ED) for management of vaso-occlusive pain events. Methods: We conducted a qualitative systematic review. The search protocol was developed to identify both published and unpublished literature that met inclusion/exclusion criteria. Included articles were primary hospital-based research with study populations that included (but were not limited to) pediatric patients aged 21 years or younger and qualitative or mixed-method analysis. Results: Four themes were identified: (1) patients and caregivers perceive the ED as the last resort; (2) health care professionals in the ED lacked knowledge about SCD but rejected patients' and caregiver's attempts to share experience or advocate for their needs; (3) patients' accounts of pain are doubted because they do not always have "typical" signs of pain; and (4) caregivers identify racism as a reason for suboptimal care in the ED. Conclusions: There are multiple opportunities to improve management for vaso-occlusive pain events in the ED, including education of health care providers about SCD and complications, partnership between patients/caregivers and providers, and efforts to reduce the impact of systemic racism on health care delivery.